Folle de Nelly Arcan (2004) : les « déterminations biologiques » dans la construction identitaire masculine - Brassard, Christina (Romanica Silesiana)
Folle by Nelly Arcan : Biological Determinants in the Construction of the Masculine Identity The reading of Folle, a novel written by Nelly Arcan, might well be an experience of disillusionment. The current analysis suggests that its principal masculine character insists on the primacy of biological factors. Through this line of thought, the reader and the contemporary thinker may want to question their perception of the construction of masculine identity as the principal masculine character is oblivious to theories of gender. He forgets that the modern human brain is not immutable and that femininity and masculinity are social constructions. For him, there is a huge gap between man and woman and this space seems to be the result of testosterone. Key words: construction of masculine identity, biological determinants, gender differences, Québécois literature, Nelly Arcan, Judith Butler, Nancy Huston.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />